2021
DOI: 10.3892/etm.2021.10061
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin relieves lipopolysaccharide‑induced acute kidney injury in mice by reducing inflammation, oxidative stress and apoptosis

Abstract: Acute kidney injury (AKI) is a serious disease with rapid onset and a high mortality rate. It is therefore particularly important to identify a suitable method for treating AKI. Thioredoxin (Trx) is a potent anti-inflammatory and anti-oxidant protein that is prevalent in living organisms. The aim of the present study was to facilitate the clinical treatment of AKI via the study of Trx. Lipopolysaccharide (LPS) was used to construct an AKI model in mice and the mice were pre-treated with Trx to examine its effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…In ROS-induced cardiomyocyte injury, Trx clears ROS and enhances mitochondrial function, preventing cardiomyocyte hypertrophy and apoptosis. There are also some data on the antioxidant and protective effects of Trx in preventing acute kidney injury [ 74 ].…”
Section: Biomarkers Of Oxidative Stress In Akimentioning
confidence: 99%
“…In ROS-induced cardiomyocyte injury, Trx clears ROS and enhances mitochondrial function, preventing cardiomyocyte hypertrophy and apoptosis. There are also some data on the antioxidant and protective effects of Trx in preventing acute kidney injury [ 74 ].…”
Section: Biomarkers Of Oxidative Stress In Akimentioning
confidence: 99%
“…Hepatic glutathione activity was significantly increased. Pan Guangtao et al [41] found that emodin can improve liver function and liver pathological changes, regulate liver oxidative stress, alleviate liver cell apoptosis, reduce the secretion of pro-apoptotic factors, and increase the expression of anti-apoptotic factors. The mechanism may be related to regulating oxidative stress and reducing hepatocyte apoptosis.…”
Section: Hepatoprotective Effectmentioning
confidence: 99%